Agile Processes in Software Engineering and Extreme Programming (Springer Nature, 2024)
This open access book constitutes the proceedings of the 25th International Conference on Agile Software Development, XP 2024, which took place in Bozen-Bolzano, Italy, during June 04-07, 2024. XP is the premier agile software development conference combining research and practice. It is a unique forum where agile researchers, practitioners, thought leaders, coaches, and trainers get together to present and discuss their most recent innovations, research results, experiences, concerns, challenges, and trends.  XP conferences provide an informal environment to learn and trigger discussions and welcome both people new to agile and seasoned agile practitioners. This year’s conference was held with the theme “Reflect, Adapt, Envision”. The 10 full and 2 short papers included in these proceedings were carefully reviewed and selected from 32 submissions. They were organized in topical sections as follows: agile at scale; value and quality in agile; and people and teams in agile.